1979
DOI: 10.1149/1.2129010
|View full text |Cite
|
Sign up to set email alerts
|

Electrooxidation of Sulfur in Molten AlCl3 ‐ NaCl ( 63 – 37   Mole Percent )

Abstract: The electrooxidation of sulfur in AlCl3‐normalNaCl false(63–37 normalmole percentfalse) has been investigated in the temperature range 150°–250°C. The oxidation of sulfur proceeds from S8 to SCl3+ and involves intermediates S8+ false(S162+false) , S82+ , and S(I).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…Primary Reactions of Aqueous Free Radicals with Platinum Complexes. Pulse irradiation of dilute aqueous solutions by high-energy electrons (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) MeV in this study) leads to the generation of aqueous free radicals, hydrogen ion, and smaller amounts of H2 and H202. H20 -eaq", H, OH, H+, H2, H202…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Primary Reactions of Aqueous Free Radicals with Platinum Complexes. Pulse irradiation of dilute aqueous solutions by high-energy electrons (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) MeV in this study) leads to the generation of aqueous free radicals, hydrogen ion, and smaller amounts of H2 and H202. H20 -eaq", H, OH, H+, H2, H202…”
Section: Resultsmentioning
confidence: 76%
“…Implied in eq 5 is the occurrence of a net decrease in conductivity due primarily to the consumption of hydroxide ion. The latter will however be partially mitigated by the rapid equilibrium NH3 + H20 ^NH4+ + OH- (6) Retaining our original premise that the formation of A! (eq 3) does not reflect a change in charge, one then anticipates from the kinetic data, overall conductivity changes of about -25 (pH 9), -120 (pH 9.7), and -170 -1 cm2 equiv-1 (pH 10).37 These values are in fair agreement with the observed ones of -30, -90, and -130 -1 cm2 equiv-1.…”
Section: Resultsmentioning
confidence: 99%
“…The electrochemistry of sulfur-polysulfide systems has been studied extensively in organic molecular solvents as well as in some molten salts, with only one work in a chloroalumimate ionic liquid (AlCl 3 -[C 4 py]Cl; C 4 py = 1-butylpyridinium) published to date . These studies have shown that the reduction of sulfur is very complicated, where one or more electron-transfer reactions followed by a series of chemical transformations occur at each reduction wave.…”
Section: Introductionmentioning
confidence: 99%
“…In chloroaluminate mixtures (e.g., AlCl 3 /NaCl , or AlCl 3 -[C 4 py]Cl ([C 4 py] + = N -butylpyridinium), the electrochemistry of elemental sulfur is further complicated by the formation of chlorinated species such as S 2 Cl 2 and SCl 3 + , with up to four oxidation and four reduction waves observed in some systems . However, reduction to S 8 2– is also proposed to occur at the first voltammetric wave in AlCl 3 /NaCl melts. , It has also been shown that elemental sulfur can be easily reduced to other sulfur species (S 6 2– or S 3 •– ) by dissolving it at certain temperature in some phosphonium and imidazolium ionic liquids …”
Section: Introductionmentioning
confidence: 99%
“…1.60 V, because such oxidation state sulfur species are easily produced in the chloroaluminate molten salts. 31,32 Considering the areal capacity (mA h cm À2 ), it is desirable to contain more SPEG in the composite material. Composites consisting of SPEG (85 wt%), KB or MWCNT (10 wt%), and PTFE (5 wt%) were prepared.…”
mentioning
confidence: 99%